Genetic Divergence of Thai Indigenous Pigs from Three Distinct Geographic Regions Revealed by Microsatellite Marker Analysis - Kamon Chaweewan; Prapas Mahinchai; Sornchai Kongsook; Surasak Soponchit; Phuree Weerasamith; Wiranphat Awiruttapanich; Pakhawan Prapawat; Warocha Jamparat; Thitawat Chanthaworn; Natinee Rattanamahavichai; Sarisa Weangchanok; Siwaret Arikit; et al. (My University, 2023)
Thai indigenous pigs (TIPs) are important genetic resources. Crosses with exotic pig breeds and wild boars may cause genetic losses. To date, the physical characteristics of TIPs have been inconsistent. The classification of TIPs by genetic information is needed to pursue an appropriate conservation program. In this study, the genetic diversity, cluster analysis, and phylogenetic relationship of TIPs were investigated using twenty-nine pig microsatellite markers. Blood samples were collected from TIPs from three regions of Thailand: north (NT, n = 118), northeast (NE, n = 61), and south (ST, n = 75). The mean total number of distinct alleles and the effective number of alleles per locus were 11.851 and 5.497, respectively. The mean observed heterozygosity (Ho) and mean expected heterozygosity (He) were 0.562 and 0.837, respectively. The F values of the microsatellite loci were positive under Hardy–Weinberg Equilibrium at p < 0.001, with overall mean values of Fis, Fit, and Fst of 0.247, 0.281, and 0.046, respectively. A total of 5, 5, and 17 private alleles were found at frequencies greater than 0.050 in the NT, NE, and ST pigs, respectively. Three optimal clusters (K = 3) were proposed within the TIP populations. Pigs from the NT and NE regions were mixed in two clusters, while members of the ST region were clearly separated. The phylogenetic tree confirmed that the pigs from NT and NE were each divided into two subgroups, while the pigs from ST were clustered into one group. A microsatellite analysis revealed the high genetic diversity of the TIP populations and confirmed the genetic divergence of the TIPs from the European and Chinese breeds. A genetic admixture of the TIP with the local wild boars was detected.
Keywords: Genetic divergence; Genetic distance; Genetic relationship; Genetic Analysis; Genetic and phenotypic traits in livestock